Sistem Informasi Pemesanan Tiket Bus pada PO. Sampri Berbasis Mobile - Senta Egrioni Sihaloho; Jamaluddin Jamaluddin; Resianta Perangin-angin (Universitas Methodist Indonesia, 2024)
PO. SAMPRI is a company engaged in the field of bus transportation services where the presentation of ticket orders, departure schedule information, and payment transactions is still manual. So that it is difficult for consumers to get bus ticket reservation information and it is less efficient in terms of time and costs because consumers have to come directly to the PO counter.SAMPRI. For this reason, a mobile-based information system for ordering bus tickets was built with the aim of providing information and services to customers regarding online ticket ordering. The methods used in this research are the field method and the system design method. The field method is divided into three parts, namely observation, interview and literature study, while the analysis system design method consists of system, system design and system implementation. The expected result is to simplify PO. SAMPRI in providing services to customers and facilitating customers in the process of ordering tickets.